Strategies to Control In Vitro Degradation of Mg Scaffolds Processed by Powder Metallurgy - Cifuentes, Sandra C.; Alvarez, Lucia; Arias, Luis; Fey, Tobias; Tsipas, Sophia A. (Metals, 2022)
Magnesium scaffolds are biodegradable, biocompatible, bioactive porous scaffolds, which find applications within tissue engineering. The presence of porosity increases surface area and enhances cell proliferation and tissue ingrowth. These characteristics make Mg scaffolds key materials to enhance the healing processes of tissues such as cartilage and bone. However, along with the increment of porosity, the corrosion of magnesium within a physiological environment occurs faster. It is, therefore, necessary to control the degradation rate of Mg scaffolds in order to maintain their mechanical properties during the healing process. Several studies have been performed to increase Mg scaffolds’ corrosion resistance. The different approaches include the modification of the Mg surface by conversion coatings or deposited coatings. The nature of the coatings varies from ceramics such as hydroxyapatite and calcium phosphates to polymers such as polycaprolactone or gelatin. In this work, we propose a novel approach to generating a protective bilayer coating on the Mg scaffold surface composed of a first layer of naturally occurring Mg corrosion products (hydroxide and phosphates) and a second layer of a homogeneous and biocompatible coating of polylactic acid. The Mg scaffolds were fabricated from Mg powder by means of powder metallurgy using ammonium bicarbonate as a space holder. The size and amount of porosity were controlled using different size distributions of space holders. We addressed the influence of scaffold pore size on the conversion and deposition processes and how the coating process influences the in vitro degradation of the scaffolds.
CRIS-Team Scopus Importer:2022-05-06
Keywords: biodegradable; in vitro degradation; Mg scaffolds; powder metallurgy